HUKUM AGRARIA DAN PERLINDUNGAN HUTAN LINDUNG DI INDONESIA - Annisa Fitratul Jannah; Sari, Mia Puspita; M. Yamani (LPPM Universitas Doktor Husni Ingratubun Papua, 2025)
Agrarian law and protected forest protection in Indonesia is a strategic issue in natural resource management that often faces conflicts between development interests, indigenous peoples' rights, and environmental conservation. This study aims to analyze the legal framework of agrarian and forestry, as well as evaluate the effectiveness of the implementation of protected forest protection policies in Indonesia. Using normative juridical methods supported by empirical studies, this study examines the Basic Agrarian Law No. 5 of 1960 and the Forestry Law No. 41 of 1999 as the main legal basis, as well as various implementing regulations. This study is expected to show that despite comprehensive regulations, the implementation of protected forest protection is often constrained by overlapping authorities, the determination of areas that do not pay attention to the rights of indigenous peoples, and weak law enforcement. Land ownership conflicts In protected forest areas is one of the main challenges, especially when cultivation rights or property rights have been granted before the area has been designated as a protected forest. In addition, it is necessary to strengthen law enforcement mechanisms and recognize the rights of indigenous peoples as an effort to create a balance between legal certainty, social justice, and environmental sustainability. These findings are expected to be an important contribution to the development of more sustainable agrarian and forestry policies in Indonesia.